Defining early education quality using CLASS-observed teacher-student interaction - Pianta, Robert C.; Hofkens, Tara (Frontiers in Psychology, 2023)
In this paper we argue that the quality of early education programs or classrooms can be defined in terms of observable features of teachers’ interactions with students. We present evidence demonstrating that dimensions of teacher-student interactions can be described, observed, and measured consistently across cultures and countries and that such dimensions also positively influence student development and learning. Evidence is summarized indicating that interactions can also be improved systematically through professional development interventions. The paper relies on a framework that describes core features of effective teacher-student interactions that appear in common across countries’ highly varied settings and cultural contexts. We discuss the cross-cultural applicability of the framework and outline suggestions for education policy and practice and future directions for research.